Sustainable Beauty: â€œWaste Down Kindness Up Sociollaâ€ Kolaborasi Sukin dengan Waste4Change dalam Upaya Pengolahan Sampah Kecantikan - Ningrum, Kheria Yulia; Risa, Naila Ananda (HK-Publishing, 2023)
AbstractThe beauty industry is a highly developed industrial sector. Not only developing economically and market, but also can even give birth to new industries through beauty enthusiasts which at this time can also develop into beauty influencers. However, behind the beauty in the beauty industry that exists today, there is a dark side that accompanies it, where the beauty industry can cause piles of waste left over from its product packaging. In addition to the mounting piles of garbage, there are other threats in the form of microbead which can damage the environment due to the rest of the product in it. As an effort to manage waste, Sociolla, Sukin and Waste4Change are trying to recycle used beauty product packaging containers through the Waste Down Kindness Up campaign. To examine this matter, research will be carried out using qualitative methods through literature study efforts.Keywords: Beauty Industry, Beauty Waste, RecycleÂ AbstrakSaat ini salah satu bidang industri yang berkembang pesat adalah industri kecantikan. Tidak hanya berkembang secara ekonomi dan pasar, tetapi juga bahkan dapat melahirkan industri baru melalui beauty enthusiast yang saat ini juga dapat berkembang menjadi beauty influencer. Namun, dibalik keindahan dalam industri kecantikan yang hadir saat ini terdapat sisi gelap yang menyertai, dimana industri kecantikan dapat menimbulkan tumpukan sampah sisa kemasan produknya. Selain tumpukan sampah yang menggunung terdapat ancaman lain berupa microbead yang dapat merusak lingkungan akibat sisa produk didalamnya. Sebagai upaya pengelolaan sampah Sociolla, Sukin, dan Waste4Change berupaya untuk melakukan recycle wadah bekas kemasan produk kecantikan melalui kampanye Waste Down Kindness Up. Untuk meneliti hal tersebut akan dilakukan penelitian menggunakan metode kualitatif melalui upaya studi literatur.Kata Kunci: Industri Kecantikan, Limbah Kecantikan, Daur Ulang